2014
DOI: 10.5770/cgj.17.95
|View full text |Cite
|
Sign up to set email alerts
|

Geriatric Core Competencies for Family Medicine Curriculum and Enhanced Skills: Care of Elderly

Abstract: BackgroundThere is a growing mandate for Family Medicine residency programs to directly assess residents’ clinical competence in Care of the Elderly (COE). The objectives of this paper are to describe the development and implementation of incremental core competencies for Postgraduate Year (PGY)-I Integrated Geriatrics Family Medicine, PGY-II Geriatrics Rotation Family Medicine, and PGY-III Enhanced Skills COE for COE Diploma residents at a Canadian University.MethodsIterative expert panel process for the deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 9 publications
1
19
0
Order By: Relevance
“…The key clinical situations and observable behaviours that the experts prioritized for senior care in the present study are consistent with those identified by others (Charles, Triscott, Dobbs, & McKay, 2014;Mezey, Mitty, Burger, & McCallion, 2008;Williams et al, 2010). For example, a recent expert consensus also identified cognitive disorders, functional decline, incontinence, medication management, and communication skills as geriatric core competencies for family medicine, converging with our findings (Charles et al, 2014).…”
Section: Competencies Associated With Senior Caresupporting
confidence: 91%
“…The key clinical situations and observable behaviours that the experts prioritized for senior care in the present study are consistent with those identified by others (Charles, Triscott, Dobbs, & McKay, 2014;Mezey, Mitty, Burger, & McCallion, 2008;Williams et al, 2010). For example, a recent expert consensus also identified cognitive disorders, functional decline, incontinence, medication management, and communication skills as geriatric core competencies for family medicine, converging with our findings (Charles et al, 2014).…”
Section: Competencies Associated With Senior Caresupporting
confidence: 91%
“…that presents core geriatric competencies for both family practice programs and specialized care of the elderly programs. (4) Naslund et al . have examined Canadian Study of Health and Aging data to demonstrate changes in health service utilization costs in the year prior to institutionalization.…”
mentioning
confidence: 99%
“…It is imperative that health care practitioners are knowledgeable in all areas of geriatric care [3]. In order to educate the next generation of health care providers, competencies have been developed by the different professions to ensure that this training process includes the essential elements needed for practice [4]. The Academy of Geriatric Physical Therapy developed a comprehensive list of competencies that physical therapists must possess upon completion of their training [5].…”
Section: Introductionmentioning
confidence: 99%